Factors associated with utilization of posyandu lansia in Indonesia: an analysis of nationwide survey data - Trisfayeti, Ica Hervita; Idris, Haerawati (Public Health and Preventive Medicine Archive, 2022)
Background and purpose: The proportion of the older population in the world is increasing, including in Indonesia. The elderlies tend to be more susceptible to infectious diseases and chronic diseases due to decreased anatomical and physiological functions. A model of health services for the elderlies in Indonesia is called posyandu lansia (integrated health village posts for older adults). This study aims to analyse the determinants of the use of health village posts among older adults in Indonesia. Methods: This study is a secondary data analysis of the 2014 Indonesian Family Life Survey (IFLS-5) data . The study samples included 4,366 respondents at the age of 50 years and over. The dependent variable is utilization of posyandu lansia and the independent variables consist of age, gender, level of education, work status and activity of daily living. Data analysis was performed using univariate, bivariate and multivariate analysis. Results: The study results show that the utilization of posyandu lansia was 5.1%. Age ≥60 years, female gender, secondary education, unemployment, region, location, activity of daily living, nutritional status of fat and thin, acute morbidity, and a history of chronic disease have a significant relationship with the utilization of posyandu lansia in Indonesia (p<0.05). Females were 3.097 times more likely to utilize posyandu lansia (95%CI: 2.464-3.891) than males. Conclusion: Women are more likely to use the posyandu lansia than men. The government should increase the effort to expand coverage of posyandu lansia utilization especially among males.